The grazing preferences of sheep on pastures containing drunken horse grass (Achnatherum inebrians) in Xinjiang province, China - Norton B.W.; Li X.S.; Fletcher I. (Nutritional and foraging ecology of sheep and goats, 2009)
Drunken horse grass (DHG) [Achnatherum inebrians (Hance) Keng] is a rapidly spreading perennial grass weed of western China. DHG contains an endophytic fungus (Neotyphodium spp.) which produces neurotoxins which cause morbidity in animals grazing these plants. The present study investigates the effects of fungicide (propiconizole) application, seed heat treatment, N and P fertiliser and water application on the growth and potential toxicity of DHG for grazing sheep in Xinjiang province of PRC. Two experiments are reported in which Merino/Xinjiang fine-wool sheep are grazed on pasture plots (5 × 10 m) of DHG and native grasses to which the above treatments were applied. Field application of fungicide did not effectively control DHG endophyte, reducing infection from 92 to 60%, and ergonovine concentrations from 358 to 273 mg/kg DM. Sheep selected other grasses in preference to DHG which formed on average 27% of DM eaten. The levels of endophyte in DHG did not affect preference, nor did the application of N and P fertiliser. In the second experiment, heat treatment of DHG seed prior to planting significantly reduced both endophyte (93 vs 5%) and ergonovine (308 vs 10 mg/kg DM) in DHG being grazed. Sheep consumed more DHG (54% removed, 61% in the diet) than did sheep grazing infected DHG pastures (38% removed, 51% in the diet). It was concluded that heat-treatment of seed is a cheap, practical and effective way of producing toxin-free DHG pastures in this area, and since neither plant survival nor responsiveness to fertiliser and irrigation was affected by endophyte presence, toxin-free DHG pastures may be a valuable new grazing resource for this low rainfall area. The present study also showed that while sheep will eat some DHG, they have a greater preference for other grasses, which increases as the proportion of other grasses in the sward increases.
12. Seminar on: Nutritional and Foraging Ecology of Sheep and Goats, 2007/10/11-13, Thessaloniki (Greece)